Food security, poverty and nutrition policy analysis: Statistical methods and applications - Babu, Suresh Chandra; Sanyal, Prabuddha (Academic Press, 2009)
Section I: Food security policy analysis -- 1. Introduction to food security: concepts and measurement -- 2. Implications of technological change, post-harvest technology and technology adoption for improved food security - application of t- Statistic -- 3. Effects of commercialization of agriculture (shift from traditional crop to cash crop) on food consumption and nutrition - application of chi-square statistic -- 4. Effects of commercialization of agriculture or technology adoption and gender of household head: The issue, its importance in food security - application of Cramer's V and phi coefficient -- 5. Changes in food consumption patterns: The issue and its importance to food security - application of one-way ANOVA -- 6. Impact of market access on food security - application of factor analysis -- Section II: Nutrition policy analysis -- 7. Impact of maternal education and care on preschoolers' nutrition - application of two-way ANOVA -- 8. Indicators and causal factors of nutrition - application of correlation analysis -- 9. Effects of individual, household and community indicators on child's nutritional status - application of simple linear regression -- 10. Female education and community characteristics as indicators of nutritional status of children - application of multivariate regression -- Section III: Special topics on poverty, nutrition, and food policy analysis -- 11. Predicting child nutritional status using related socio-economic variables - application of discriminant function analysis -- 12. Measurement and determinants of poverty - application of logistic regression models -- 13. Classifying households on food security and poverty dimensions - application of K-mean cluster analysis -- 14. Household care as a determinant of nutritional status - application of instrumental variable estimation -- 15. Achieving an ideal diet - modeling with linear programming -- Technical appendices -- Statistical tables.